Selective Dimerization of Lewis‐Acid/Base‐Stabilized Phosphanylalanes. Issue 3 (23rd November 2012) - Bodensteiner, Michael; Timoshkin, Alexey Y.; Peresypkina, Eugenia V.; Vogel, Ulf; Scheer, Manfred
Abstract The reaction of [(CO)5WPRH2] (R=H, Ph) with H3Al⋅NR3 (R=Et, Me) leads to the formation of four‐membered heterocyclic compounds [((CO)5WP(H)AlH⋅ NEt3)2] and [((CO)5WPhPAlH⋅ NMe3)2]. Upon dissolving the solid compounds, fast equilibria between the isomers are observed on the NMR timescale. Further insight into the stability and reactivity of the isomers was gained by applying theoretical methods. DFT calculations predict that hydrogen elimination in the case of [((CO)5WPhPAlH⋅NMe3)2] may be reversible.